ELIMINASI HARMONIK GUNA PERBAIKAN BENTUK GELOMBANG KELUARAN TEGANGAN INVERTER - Sukmawidjaja, Maula (Jurnal Teknik Elektro, 2006)
The output-voltage waveform of an inverter is non sinusoidal and in most applications thevoltage harmonics have a significant effect on the overall system performance. Theseharmonics may be reduced at the cost of increasing the complexity of the inverter circuit,and an economic decision must be made on the degee to which this should be done. The Twomost commonly used techniques for harmonic-reduction are presented in this paper, theseare harmonic reduction by Pulse-Width Modulation and Sinusoidal Pulse-WidthModulation.Keyword: harmonic-reduction, Pulse-Width Modulation, Sinusoidal Pulse-WidthModulation.